Pelatihan Pembuatan Video Pembelajaran pada Guru SD IT Al-Iffat Payakumbuh Menggunakan Aplikasi OBS Studio - Sari, Dian Permata; Buana, Wira; Sari, Mike Febri Mayang; Rizki, Sestri Novia (PUAN INDONESIA, 2025)
As time progresses, especially in terms of technology, there are more and more benefits that can be obtained if we can keep up. Currently, especially in the midst of the COVID-19 pandemic, the teaching and learning process has also changed. The world of education was then forced to change direction to change the way of learning based on face-to-face encounters to online learning. If previously you were used to providing material through books, now teaching materials are provided via online media, which can be in the form of e-books, digital classes, or learning videos. Currently, learning media is developing very rapidly, previously using textbooks, teaching in class and now using online media. The use of online media in learning can be in the form of audio and video learning which students can access anywhere and anytime, regardless of time. Technological advances in the world of education must be balanced with the quality of teachers regarding understanding and expertise in using technology so that students do not become monotonous in learning with the online system. Learning videos are media that can be used to support the smooth learning process, one application that can be used is Open Broadcaster Software (OBS) studio. Some of the features of this application are recording. Apart from that, the application can be used for streaming by having scene, visual and audio features that can be created with the creativity of each teacher. With video learning media, students are able to achieve abilities in the cognitive, affective, psychomotor domains and can improve interpersonal skills.